Application of Scanning Electron Microscopy/Energy-Dispersive X-Ray Spectroscopy for Characterization of Detrital Minerals in Karst Cave Speleothems. (25th February 2016) - Zupančič, Nina; Miler, Miloš; Šebela, Stanka; Jarc, Simona
Abstract: Micro-scale observations in karst caves help to identify different processes that shaped local morphology. Scanning electron microscopy/energy-dispersive X-ray spectroscopy inspection of speleothems from two karst caves in Slovenia, Predjama and Črna Jama, confirmed the presence of sub-angular to sub-rounded detrital fragments of clay minerals, feldspars, quartz, Fe-oxides/hydroxides, rutile and Nb-rutile, xenotime, kassite, allanite, fluorapatite, epidote, ilmenite, monazite, sphene, and zircon, between 2 and 50 μ m across. These occur in porous layers separating calcite laminae in the clayey coating on the layer below the surface of the speleothems, and are also incorporated within actual crystals. It is likely that they are derived from the weathered rocks of the Eocene flysch. Probably they were first transported into the caves by floodwaters forming cave sediments. Later, depending upon the climate conditions, they were moved by air currents or by water to the surface of active speleothems. They might also be redeposited from overlying soils enriched with wind-transported minerals from the flysch, or from higher passages filled with weathered flysch sediment, by drip water percolating through the fissured limestone. As some of the identified minerals are carriers of rare earth elements, Ti and Zr, their presence could affect any palaeoclimatic interpretations that are based upon the geochemical composition of the speleothems.